2011
DOI: 10.1007/978-0-85729-352-7_14
|View full text |Cite
|
Sign up to set email alerts
|

Attentional Behavior of Users on the Move Towards Pervasive Advertising Media

Abstract: Abstract:In this chapter we analyze the attention of users on the move towards pervasive advertising media. We report the findings of two multi-sensor eye tracking studies designed to provide a better understanding of the actual attentional behavior of users on the move in different public environments. In the first study 106 participants were equipped with eye tracking technology and asked to use public transportation vehicles equipped with information and advertising screens. In a second study 16 participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
0
13
0
1
Order By: Relevance
“…Significantly more work needs to be carried out to understand the relative contribution of task and context on patterns of looking at displays and other kinds of situated technologies in a variety of real world environments (cf. [29]). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Significantly more work needs to be carried out to understand the relative contribution of task and context on patterns of looking at displays and other kinds of situated technologies in a variety of real world environments (cf. [29]). …”
Section: Resultsmentioning
confidence: 99%
“…Although these findings are useful in establishing the utility of such displays on public transport, it is unlikely that the same patterns of engagement would be evident in other contexts; those travelling are likely to be actively searching for an activity to occupy their time or travel information and may be motivated to view the displayed content in a way that those walking through a shopping centre, for example, may not be. Schrammel et al [29] conducted a study of participants' eye movements while walking through a shopping street, finding most held a relatively steady gaze in the horizontal middle of the field of view, with a greater orientation to the direction of the shops, which were located to the right of the street. However, research has shown gaze to be highly influenced by the demands of the task (e.g.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Multitasking and support for task interruption are of high relevance, since in a mobile context the frequency of distracting events is much higher than for a desktop application and tasks with interruptions take longer to complete on a mobile device than with a desktop application [4]. Special interest is therefore on increased competition with regard to attracting the users' attention and on interaction as a non-primary task in a certain context [5]. However, current technologies for the mapping of point-of-regards (PORs) to mobile displays do not enable natural interaction with the mobile device: users of the mobile device are either conditioned to act with tightly mounted displays and hence prevented from performing in the typical mobile user's environment or they are distracted by markers in the view ( Figure 3).…”
Section: Introductionmentioning
confidence: 98%
“…Mobile eye tracking technologies have been used to address this problem, e.g. [11]. Unfortunately, eye tracking is resource intensive and has several other disadvantages (e.g.…”
Section: Introductionmentioning
confidence: 99%